On the Sitnikov‐like N‐body problem with quasi‐homogeneous potential. Issue 5 (8th July 2021) - Suraj, Md Sanam; Aggarwal, Rajiv; Aggarwal, Vipin Kumar; Asique, Md Chand; Mittal, Amit
Abstract: In the present article, the periodic solutions of the N ‐body with quasi‐homogeneous potential in the Sitnikov sense by applying the multiple methods of scale (MMS) and Lindstedt–Poincaré (LP) technique are obtained. However, these methods are used to find the approximate periodic solutions in the closed form by eliminating the secular terms. In addition of the Newtonian potential and forces, we consider that the big bodies create quasi‐homogeneous potentials. We add the inverse cubic corrective term to the inverse square Newtonian law of gravitation, in order to approximate the various phenomena due to the shape of the bodies or the radiation emitting from them. We study the Sitnikov motion in the N ‐bodies under this consideration. We, further, analyzed the obtain approximate periodic solutions of the Sitnikov motion, for ν = 2, 7 by using the MMS and LP‐method, in closed form. The numerical comparisons are presented in the first and second approximated solutions obtained by using MMS and numerical solutions obtained by LP‐method are illustrated graphically. The effect of initial conditions on the solutions of the Sitnikov motion is illustrated graphically obtained by both the techniques. It is observed that the choice of initial conditions plays a crucial role in the numerical and approximate solutions.